2011
DOI: 10.1002/pola.24830
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high molecular weight polymer nanoparticles by [Cp2ZrCl2] catalyzed emulsion polymerization

Abstract: An early transition metal metallocene compound, Cp2ZrCl2, with an anionic surfactant, sodium n‐dodecyl sulfate (SDS) as emulsifier and NaBPh4 as cocatalyst has been found to be an effective catalytic system for polymerization and copolymerization of monomers like styrene and methyl methacrylate in aqueous medium. The diameters of the latex particles were found to be in between 20 and 40 nm. © 2011 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2011

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[28][29][30][31] Organo-titanium (III) species, which are readily obtained by the reduction of inexpensive Cp 2 TiCl 2 with Zn, have been reported to catalyze styrene, substituted styrene or conjugated diene living radical polymerization initiated by epoxides, peroxides or aldehydes. [28][29][30][31] In the literature, a few articles by Bhattacharjee et al [32][33][34][35][36] have described the use of Cp 2 MCl 2 (with Cp ¼ cyclopentadienyl and M ¼ Ti, Zr) as an active catalytic precursor for the aqueous emulsion homopolymerization of styrene and methylmethacrylate. This Cp 2 MCl 2 -catalyzed reaction produced stereoirregular polymers that had high molecular weights.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[28][29][30][31] Organo-titanium (III) species, which are readily obtained by the reduction of inexpensive Cp 2 TiCl 2 with Zn, have been reported to catalyze styrene, substituted styrene or conjugated diene living radical polymerization initiated by epoxides, peroxides or aldehydes. [28][29][30][31] In the literature, a few articles by Bhattacharjee et al [32][33][34][35][36] have described the use of Cp 2 MCl 2 (with Cp ¼ cyclopentadienyl and M ¼ Ti, Zr) as an active catalytic precursor for the aqueous emulsion homopolymerization of styrene and methylmethacrylate. This Cp 2 MCl 2 -catalyzed reaction produced stereoirregular polymers that had high molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…This Cp 2 MCl 2 -catalyzed reaction produced stereoirregular polymers that had high molecular weights. [32][33][34][35][36] Moreover, in these reports, it has been hypothesized that the active catalytic species could be a cation such as [Cp 2 MOH] þ , which is one of the species formed by the hydrolysis of Cp 2 MCl 2 , 37 stabilized by the large non-coordinating anion n-dodecylsulfate and utilized as an emulsifier. [32][33][34][35][36] Although the polymerization mechanism has not been definitively determined, the authors suggested that the polymerization reaction start by insertion of a monomer into the 'labile' metal-hydroxyl group bond, which excludes the possibility of free radical or spontaneous polymerization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations